Psychometric properties of post-traumatic stress disorder (PTSD) checklist for DSM-5 in persons with serious mental illness. Issue 1 (31st December 2022) - Lu, Weili; Yanos, Philip T.; Waynor, William; Jia, Yuane; Siriram, Amanda; Leong, Alyssa; Gill, Kenneth; Mueser, Kim T.
ABSTRACT: Background: PCL-5 is a self-report measure consisting of 20 items that are used to assess the symptoms of Post-Traumatic Stress Disorder (PTSD) according to the DSM-5. Objective: This study evaluated the factor structure of the Post-Traumatic Stress Disorder (PTSD) Checklist for DSM-5 (PCL-5) in people with serious mental illness. Method: The sample in Study 1 included 536 participants with serious mental illness who were receiving supported employment services through community mental health agencies or supported housing programmes. Confirmatory factor analysis assessed the fit of six different models of PTSD. Results: Results indicated that Armour's Hybrid 7-factor model composed of re-experiencing, avoidance, dysphoria, dysphoric arousal, anxious arousal, negative affect, anhedonia, and externalizing behaviours demonstrated the best fit. Study 2 found support for convergent validity for PCL-5 among 132 participants who met criteria for PTSD. Conclusion: Findings provide support for the psychometric properties of the PCL-5 and the conceptualization of the 7-factor hybrid model and the 4-factor DSM-5 model of PTSD among persons living with serious mental illness. HIGHLIGHTS: This study evaluated the factor structure of the Post- Traumatic Stress Disorder (PTSD) Checklist for DSM-5 (PCL-5) in people with serious mental illness (SMI). Findings support the psychometric properties of the PCL-5 and the seven- symptom-clusters of PTSD in persons with SMI. The PCL-5 was found to be psychometrically sound among persons with psychiatric diagnoses receiving community mental health services, as evidenced by excellent internal consistency and convergent/divergent validity for both the 4-factor DSM-5 model and the 7-factor model of PTSD.